The species composition of amphibians and reptiles in Dong Thap province - Chung, Ngo Dac; Nghiep, Hoang Thi (Academia Journal of Biology, 2014)
The list of Herpetology in Dongthap is presented in this article. Dongthap province is the province in the Mekong delta region of Southern in Vietnam. It is located at 10o10’02” - 11o11’00” N, 105o10’00” - 105o60’00” E. We collected specimens from August 2004 to June 2006 around 11 regions of Dongthap, the time of the discovery divided into 5 times: August 2004, June 2005, August 2005, Janurary 2006 and May 2006. Caolanh city, Sadec town and nine districts: Tanhong, Hongngu, Tamnong, Thanhbinh, Thapmuoi, Caolanh, Lapvo, Laivung, Chauthanh are places for collecting of specimens. A total 69 species, including 22 species of Amphibian and 47 species of Reptile were recorded in Dongthap province, belong to 43 genus, 18 families, 5 orders and 2 classes. In that, the Squamata: Colubridae, Limnonectes having the number of species is the most plentyful. 30 species of them are predominant in this area. There were 37 precious species. 19 species of them were listed in the Red Data Book of Viet Nam (2004), and 26 species in the IUCN Red List of Threatened Animals (2006), 11 species listed in CITES appendix II, 10 species listed in Governmental Degree No. 32/2006/ND - CP (dated 30/3/2006). 4 species of reptile were belong level CR: Crocodylus siamensis, Python molurus, Python reticulatus, Ophiophagus hannah. With 69 species were described above, 68 species were first recorded in Dongthap province and 34 species are popular (49.28% of the list).